The Effect of Social Media Use Intensity on Motivation-Mediated Learning Concentration: SEM Method - Guntur Gunawan (International Journal of Education Research and Development, 2026)
This study aims to analyze the influence of the intensity of social media use on student learning concentration with learning motivation as a mediating variable. The study uses a quantitative approach with an explanatory survey design. The sample amounted to 100 students, which was determined through the quota sampling technique. The research instruments were compiled based on indicators of social media use intensity, learning motivation, and learning concentration that have been developed from relevant literature. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with a bootstrapping procedure to test the significance of direct and indirect influence paths. The results of bootstrapping analysis showed that the intensity of social media use had a positive and significant effect on learning motivation (β = 0.506; T = 4.415; p < 0.001). Learning motivation also had a positive and significant effect on learning concentration (β = 0.812; T = 17.084; p < 0.001). In addition, the indirect effect of the intensity of social media use on learning concentration through learning motivation was also significant (β = 0.411; T = 3,883; p < 0.001), which indicates partial mediation. In conclusion, the intensity of the use of social media can increase students' learning concentration both directly through increasing learning motivation and through motivational mediation mechanisms. This shows that educators and policymakers must adopt an effective way of incorporating social media within the educational setting in order to motivate the learners and help them focus.